Jagged Ends of Urinary Cell-Free DNA: Characterization and Feasibility Assessment in Bladder Cancer Detection - Zhou, Ze; Cheng, Suk Hang; Ding, Spencer C; Heung, Macy M S; Xie, Tingting; Cheng, Timothy H T; Lam, W K Jacky; Peng, Wenlei; Teoh, Jeremy Y C; Chiu, Peter K F; Ng, Chi-Fai; Jiang, Peiyong; et al. (Clinical chemistry (Baltimore, Md.), 2021)
Abstract Background Double-stranded DNA in plasma is known to carry single-stranded ends, called jagged ends. Plasma DNA jagged ends are biomarkers for pathophysiologic states such as pregnancy and cancer. It remains unknown whether urinary cell-free DNA (cfDNA) molecules have jagged ends. Methods Jagged ends of cfDNA were detected by incorporating unmethylated cytosines during a DNA end-repair process, followed by bisulfite sequencing. Incorporation of unmethylated cytosines during the repair of the jagged ends lowered the apparent methylation levels measured by bisulfite sequencing and were used to calculate a jagged end index. This approach is called jagged end analysis by sequencing. Results The jagged end index of urinary cfDNA was higher than that of plasma DNA. The jagged end index profile of plasma DNA displayed several strongly oscillating major peaks at intervals of approximately 165 bp (i.e., nucleosome size) and weakly oscillating minor peaks with periodicities of approximately 10 bp. In contrast, the urinary DNA jagged end index profile showed weakly oscillating major peaks but strongly oscillating minor peaks. The jagged end index was generally higher in nucleosomal linker DNA regions. Patients with bladder cancer (n = 46) had lower jagged end indexed of urinary DNA than participants without bladder cancer (n = 39). The area under the curve for differentiating between patients with and without bladder cancer was 0.83. Conclusions Jagged ends represent a property of urinary cfDNA. The generation of jagged ends might be related to nucleosomal structures, with enrichment in linker DNA regions. Jagged ends of urinary DNA could potentially serve as a new biomarker for bladder cancer detection.